2018
DOI: 10.1186/s12881-018-0689-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel compound heterozygous mutation in VARS2 in a newborn with mitochondrial cardiomyopathy: a case report of a Chinese family

Abstract: BackgroundGenetic defects in the mitochondrial aminoacyl-tRNA synthetase are important causes of mitochondrial disorders. VARS2 is one of the genes encoding aminoacyl-tRNA synthetases. Recently, an increasing number of pathogenic variants of VARS2 have been reported.Case presentationWe report the novel compound heterozygous pathogenic VARS2 mutations c.643 C > T (p. His215Tyr) and c.1354 A > G (p. Met452Val) in a female infant who presented with poor sucking at birth, poor activity, hyporeflexia, hypertonia, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Position 390 is highly conserved (Figure 1D). Position 390 corresponds to the tRNA-synthetase domain and position 920 corresponds to the anticodon binding domain of the protein VARS2 (1,12). These findings support the pathogenicity of the variants found in our patient.…”
Section: Molecular Genetics Findingssupporting
confidence: 88%
See 2 more Smart Citations
“…Position 390 is highly conserved (Figure 1D). Position 390 corresponds to the tRNA-synthetase domain and position 920 corresponds to the anticodon binding domain of the protein VARS2 (1,12). These findings support the pathogenicity of the variants found in our patient.…”
Section: Molecular Genetics Findingssupporting
confidence: 88%
“…Dysfunction of the protein product is responsible for combined oxidative phosphorylation deficiency 20 (OMIM: # 615917) inherited in an autosomal recessive manner. Rare biallelic variants in the VARS2 gene have been associated with severe clinical features as mitochondrial encephalomyopathy or encephalocardiomyopathy in 23 affected individuals from 19 families worldwide (1,4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In the present paper we describe a compound heterozygous case with a recurrent c.1168G>A (p.Ala390Thr) and a novel missense variant c.2758T>C (p.Tyr920His) in the VARS2 gene causing isolated hypertrophic cardiomyopathy, hyperlactatemia, and pulmonary hypertension leading to early death.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The present study reported that the clinical and molecular characterization of a Chinese pedigree with maternally inherited hypertension. Although many studies revealed the genetics of mitochondrial disorders, the molecular mechanism underlying hypertension remains unclear (22,23). Experimental studies identified a positive association between mtDNA mutations and hypertension (24,25).…”
Section: Discussionmentioning
confidence: 99%
“… 42 Several studies have focused on mitochondrial dysfunction and its role in HCM pathogenesis. 43 , 44 The previously reported pathogenic mutation of the tRNA-modifying enzyme GTPBP3 may contribute to mitochondrial dysfunction, altering embryonic heart development and reducing fractional shortening of ventricles in zebrafish. This study highlighted the role of defective nucleotide modifications of tRNAs in the pathogenesis of HCM.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%